2009
DOI: 10.4038/cocos.v2i0.811
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the pre-nursery system for raising coconut seedlings

Abstract: A pre-nursery system fur raising coconut seedlings was compared with the conventional nursery. The two major refinements introduced in the pre-nursery system are the slicing of seed nuts and transplanting of sprouted seed nuts from pre-nursery beds to nurserv beds, soon after sprouting. The rate of sprouting in the Pre-nursery system was significantly superior. At the end of 20 weeks 76% of the seednuts in the pre-nursery had sprouted as compared to 67% in the conventional nursery. However, the number of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Hence, clustering the seed nuts with space of 5 cm between them is good enough to save space and other resources. This finding is in line with that of Eufemia andRebecco 1980 andPeries, 1984 which stated that germination rate and cost of raising coconut in the nursery was different at 25 × 25 cm from those planted with spacing of 40 × 40; 60 × 60 and 80 × 80 cm. There was significant difference in the germination parameters between the sorted and unsorted seed nuts.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, clustering the seed nuts with space of 5 cm between them is good enough to save space and other resources. This finding is in line with that of Eufemia andRebecco 1980 andPeries, 1984 which stated that germination rate and cost of raising coconut in the nursery was different at 25 × 25 cm from those planted with spacing of 40 × 40; 60 × 60 and 80 × 80 cm. There was significant difference in the germination parameters between the sorted and unsorted seed nuts.…”
Section: Discussionsupporting
confidence: 90%
“…The long dry spell experienced during the germination period would have further enhanced the process of drying. In an early experiment where entry of water into husk was facilitated through partial slicing itpromoted the rate of germination (Peries, 1984) which supports this argument.…”
Section: The Temporal Change In Percentage Germination Of Seed Nuts Isupporting
confidence: 57%
“…The seed nuts were dipped in a 10% solution of Aldrin prior to laying to prevent termite attack. The beds were mulched with dry coconut fronds and irrigated once in three days during dry weather (Peries, 1984). Manual weeding was carried out at the onset of the dry weather.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, where the management of seed beds was maintained at optimum level, very little difference was obtained between sites except those due to the superiority of the source of nuts. Germination can be adversely affected by lack of water in the seed nut which is very likely to be aggravated in the absence of adequate watering (Wuidart, 1984;Peries, 1984). Remison and Mgbeze (1987) observed that the use of a mulch to conserve water in the coconut seed beds led to increased plant height, plant girth and dry matter yield.…”
Section: Methodsmentioning
confidence: 99%